At Home Inside : A Daughter's Tribute to Ann Petry - Petry, Elisabeth (Book collections on Project MUSE., 2008)
Ann Petry (1908-1997) was a prominent writer during a period in which few black writers were published with regularity in America. Her novels The Street, Country Place, and The Narrows, along with a collection of short stories and various essays and works of nonfiction, give voice to black experience outside of the traditional strains of poverty and black nationalism. At Home Inside: A Daughter's Tribute to Ann Petry sifts the myriad contradictions of Ann Petry's life from a daughter's vantage. Ann Petry hoarded antiques but destroyed many of her journals. She wrote, but, failing to publish.